2017
DOI: 10.1016/j.celrep.2017.06.090
|View full text |Cite
|
Sign up to set email alerts
|

WBSCR16 Is a Guanine Nucleotide Exchange Factor Important for Mitochondrial Fusion

Abstract: SUMMARY Regulated inter-mitochondrial fusion/fission is essential for maintaining optimal mitochondrial respiration and control of apoptosis and autophagy. In mammals, mitochondrial fusion is controlled by outer membrane GTPases MFN1 and MFN2, and by inner membrane GTPase OPA1. Disordered mitochondrial fusion/fission contributes to various pathologies, and MFN2 or OPA1 mutations underlie neurodegenerative diseases. Here, we show that the WBSCR16 protein is primarily associated with the outer face of the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…To reconcile the difference in mouse and human ATP synthase dimerization, we searched the literature and came across a report that identified RCC1L as a guanine nucleotide exchange factor for OPA1, the known mitochondrial fusion protein (Cipolat et al, 2004; Huang et al, 2017). This report showed that decreased RCC1L can phenocopy mitochondrial defects observed in Opa1 knockout cells, which themselves can exhibit decreased ATP synthase dimers and dissociation of OXPHOS supercomplexes (Cogliati et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…To reconcile the difference in mouse and human ATP synthase dimerization, we searched the literature and came across a report that identified RCC1L as a guanine nucleotide exchange factor for OPA1, the known mitochondrial fusion protein (Cipolat et al, 2004; Huang et al, 2017). This report showed that decreased RCC1L can phenocopy mitochondrial defects observed in Opa1 knockout cells, which themselves can exhibit decreased ATP synthase dimers and dissociation of OXPHOS supercomplexes (Cogliati et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, RCC1L V1 does not contain any RNA modifying domain and therefore its effect on 16S rRNA might be through the interaction with pseudouridylation proteins. There are two possible scenarios for this interaction: (i) RCC1L V1 directly regulates the steady-state levels and/or activity of pseudouridylation proteins by an unknown mechanism or (ii) most likely RCC1L V1 , through its GDP/GTP nucleotide exchange factor activity [ 22 ], regulates certain mtLSU GTPases that would act upon pseudouridylation proteins. Out of the three GTPases described to be involved in mtLSU biogenesis, MTG1, MTG2 and GTPBP10, our results pointed towards the latter as the most likely candidate.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup includes three additional members: RCC1, a GEF for the GTPase Ran [ 16 ], RCC2 (TD60), a deactivator of the GTPase Rac1 that switches its GTP for GDP [ 17 ] and DelGEF, a less characterized protein involved in regulating the GTP binding to one of the GTPases of the secretion Sec6/8 complex [ 18 ]. In mammals, RCC1L has been identified either as a component of the so called “mitochondrial pseudouridylation module”, a set of proteins involved in pseudouridylating 16S rRNA (TRUB2, RPUSD3, RPUSD4, NGRN, FASTKD2) and interacting with the mitoribosome mtLSU [ 19 ] [ 20 ] [ 21 ] [ 11 ] or as GEF for the mitochondrial fusion GTPase OPA1 [ 22 ]. However, very little attention has been paid to the fact that three different isoforms originated by alternative splicing have been identified for RCC1L, RCC1L V1-3 , all of them sharing the same N-terminus and, therefore, all three predicted to be mitochondrial [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mice heterozygous for the mutation are shown to have neuronal mitochondria with reduced membrane potential and increased susceptibility to mitochondrial fragmentation in response to excitotoxic stress. Implications of the data are discussed [118] OPA…”
Section: Williams-beuren Syndrome Multigene Deletionmentioning
confidence: 99%